2016
DOI: 10.1590/1516-4446-2015-1776
|View full text |Cite
|
Sign up to set email alerts
|

Interview-based assessment of cognition is a strong predictor of quality of life in patients with schizophrenia and severe negative symptoms

Abstract: Objective: To analyze the correlation between quality of life, symptoms, and cognition assessed by the interview-based Schizophrenia Cognition Rating Scale (SCoRS). Methods: Seventy-nine outpatients diagnosed with schizophrenia were evaluated with the Quality of Life Scale -Brazilian version (QLS-BR), the SCoRS, and symptoms scales (Positive and Negative Syndrome Scale [PANSS]). After determining the potential explanatory variables using Spearman's correlation and Student's t test results, we ran simple, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…In one study, 28 the results demonstrated that the best predictors of quality of life are negative symptoms and cognitive deficits. Better QLS results were found in patients with fewer negative symptoms regardless of the results of the Schizophrenia Cognition Rating Scale (SCoRS).…”
Section: Resultsmentioning
confidence: 99%
“…In one study, 28 the results demonstrated that the best predictors of quality of life are negative symptoms and cognitive deficits. Better QLS results were found in patients with fewer negative symptoms regardless of the results of the Schizophrenia Cognition Rating Scale (SCoRS).…”
Section: Resultsmentioning
confidence: 99%
“…Significant negative associations between symptoms and QoL in patients with psychosis have been reported in a first-episode [35] and through the short [36] and long [37,38] course of illness. Research has been performed in samples from diverse countries as United Kingdom [39], Italy [38], Greece [18], Austria [11], India [35], Japan [20], Chile [40] and Brazil [41], reflecting a world growing scientific interest to study the link between psychiatric symptoms and QoL. Yet, the reported findings concerning the patterns of these associations are quite diverse and thus, further analyses are required.…”
Section: Discussionmentioning
confidence: 99%
“…delusions, hallucinations, conceptual disorganization) the self-perceived QoL cannot be reliably measured; thus, samples exclude these patients and that might well explain the weak, though significant, positive symptom -QoL association. Negative symptoms influence QoL [17,39,41,[43][44][45], even more than positive symptoms [35,43]. It has been observed that the association between negative symptoms and QoL is related primarily to experiential deficits (i.e.…”
Section: Comparison Of Correlations Between Symptom Dimensions and Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Already the disease itself has a tremendous impact on the life of affected individuals [54] . Additionally, they suffer enormously under the cognitive impairments with a strong impact on their quality of life [55][56][57] . Until today there is no psychopharmacological treatment available for cognitive deficits.…”
Section: Why Is Research On This Complex Topic Worthwhile?mentioning
confidence: 99%